Back Cover: A simplified PDMS microfluidic device with a built‐in suction actuator for rapid production of monodisperse water‐in‐oil droplets. Issue 24 (17th December 2020) - Nakatani, Masaya; Tanaka, Yugo; Okayama, Shotaro; Hashimoto, Masahiko
Abstract : DOI: 10.1002/elps.202000105 The back cover picture shows a microfluidic device comprising a degassed PDMS slab with microchannels on one surface and micropillars on the other surface. The slab was sandwiched between PMMA layers. The large surface area‐to‐volume ratio of the micropillars (which were created by laser ablation) generated a high vacuum inside the device, leading to fast liquid flow in the channels. Consequently, this device enabled the rapid production of monodisperse water‐in‐oil droplets at a rate of >1000 droplets per second.